TINJAUAN SOSIO-LEGAL ATAS KONTRAK: KAJIAN TENTANG KETERIKATAN SOSIAL (SOCIAL EMBEDDEDNESS) DAN KETERIKATAN INSTITUSIONAL (INSTITUTIONAL EMBEDDEDNESS) PADA PENEGAKAN KONTRAK - Prabantarikso, Mahelan (Mimbar Hukum, 2024)
Abstract The theory of contracts is a fundamental element in legal theory that underpins how agreements are made and enforced. The philosophical roots of traditional contract theory essentially rely on the fiction of freedom to contract and pacta sunt servanda. Grounded in classical liberalism, traditional contract theory is based on a vacuum of ceteris paribus and individual autonomy, relating to the assumptions and fiction of freedom to contract as well as individual capacity to comply with and enforce contracts between the contracting parties. The law-in-action school in socio-legal studies encourages legal scholars to understand and consider the context in which contracts exist. There are institutional environments and social contexts that play a crucial role in contracting practices, which from a Weberian perspective, is fundamentally an economic action that must be understood in a broader context. Economic actions within those institutional and social contexts are well conceptualized in the models of New Institutional Theory, both in the school of institutional economics and organizational/institutional sociology, which fundamentally frames economic actions within formal institutional environments (institutional embeddedness) and the social networks/mechanisms that form informal institutions (social embeddedness). This framework ultimately aids in more holistically studying the fairness and effectiveness of contract enforcement. Abstrak Teori kontrak adalah elemen fundamental dalam teori hukum yang menjadi fondasi di mana perjanjian dibuat dan ditegakkan. Akar filosofis teori kontrak tradisional pada dasarnya mendasarkan pada fiksi kebebasan berkontrak dan pacta sunt servanda. Berpijak pada liberalisme klasik, teori kontrak tradisional menyandarkan pada ruang hampa ceteris paribus dan otonomi individu, berkaitan asumsi dan fiksi kebebasan berkontrak serta kapasitas individual dalam mematuhi dan menegakkan kontrak di antara pihak-pihak yang berkontrak. Mazhab law-in-action dalam kajian sosio-legal menggugah kalangan yuris untuk memahami dan menimbang konteks di mana kontrak itu hidup. Ada lingkungan institusional dan konteks sosial memainkan peran penting dalam praktik berkontrak, yang dalam pandangan Weberian, hakikatnya adalah suatu tindakan ekonomi (economic action) yang harus dipahami secara lebih luas konteksnya. Tindakan ekonomi dalam lingkungan institusional dan konteks sosial itu dikonseptualisasikan dengan baik dalam model-model Teori Institusional Baru (New Institutional Theory), baik dalam mazhab ekonomi institusional atau sosiologi organisasi/institusional, yang pada dasarnya ada dasarnya memerangka tindakan ekonomi dalam lingkungan institusional formal (institutional embeddedness) dan jaringan/mekanisme sosial yang membentuk institusi informal (social embeddedness). Kerangka tersebut pada akhirnya membantu untuk secara lebih holistik mempelajari keadilan dan efektivitas penegakan kontrak.